Motivasi Kerja, Kepuasaan Kerja, dan Komitmen Organisasional Melalui Pengukuran JDI dan WEIMS - Stefanus Rumangkit (Jurnal Ekonomi dan Manajemen, 2018)
This study aims to see the impact of work motivation and work satisfaction on organizational commitment. Respondents in this research are lecturers (lecturers) at one of the universities in Bandar Lampung. Respondents in this study amounted to 91 people. Measurement of work motivation using work exterinsic and interisic motivation scale (WEIMS), and work satisfaction is measured by job descriptive index (JDI). Data analysis in this study used multiple regression, as well as for hypothesis testing using T test. The findings of this research are: work motivation has an effect on organizational commitment, and work satisfaction is antecedent or form of organizational commitment. This shows that work motivation and work satisfaction can increase employee work satisfaction.